Structural evolution of a Ni/NiOx based supercapacitor in cyclic charging-discharging: A polarized neutron and X-ray reflectometry study. (10th November 2018) - Li, Zhe; Liu, Xinzhi; Causer, Grace L.; Lin, Ko-Wei; Pong, Philip; Holt, Stephen A.; Klose, Frank; Li, Yang Yang
Abstract: Ni/Ni-oxide based supercapacitors with their excellent stability and long cycle lifetime are favorable due to their cost effectiveness and practicality. And yet, the full picture of their cyclic charging-discharging process is not well understood, and the influential factors on the cycle life of a supercapacitor are complicated. Using a combined polarized neutron and X-ray reflectometry approach, we have studied the structural evolution of a layered Ni/NiOx supercapacitor electrode, operated in an alkaline electrolyte for cyclic charging-discharging. For the lower thousands of cycles, oxidation of Ni current-collecting backbone and dissolution of outer Ni oxide electroactive materials contribute to a total thickness consumption of 2 nm. Upon higher thousands of cycles, the two-dimensional NiOx surface-layer evolves into a three-dimensional porous network as a result of the "hole drilling" depletion behavior of Ni oxide, i.e., dissolution of the "more porous" part and preservation of the "more compact" part in the NiOx layer. The extra surface area of the Ni/NiOx supercapacitor generated after cyclic charging-discharging gives rise to an increased capacitance. Evidenced by the increased derived density, the crystal defects of inner-layer NiOx are also eliminated with cycling, probably through Ni atom rearrangement, filling of oxygen vacancies within NiOx, or both. Highlights: A Ni/NiOx supercapacitor is studied by polarized neutron and X-ray reflectometry. The depletion of electrode layers during charging-discharging is measured. The structural evolution from compact layers to a porous network is observed. The compositional change caused by crystal defect elimination is monitored.